Assessing women's empowerment in agricultural research - Elias, Marlène; Cole, Steven M.; Quisumbing, Agnes R.; Valencia, Ana Maria Paez; Meinzen-Dick, Ruth S.; Twyman, Jennifer (International Food Policy Research Institute, 2021)
The concept of empowerment has steadily made its way onto the international development agenda. Batliwala (2007) traces its equivalents back several hundred years and across geographies in struggles for social justice. Feminists brought the concept of women’s empowerment to the 1995 Fourth World Conference on Women in Beijing, where it gained traction, with the Beijing Declaration referring to “enhancing further the advancement and empowerment of women all over the world” (UN 1995, 7). Then, it was about collective struggles to challenge patriarchal structures, and intersecting structures of class, ethnicity, caste, and race, that shape women’s (subordinate) position in society (Batliwala 2007). Twenty years later, “empowerment” animates the fifth Sustainable Development Goal (SDG5): “Achieve gender equality and empower all women and girls.”